Movement demands and injury characteristics in under-20-years university rugby union players - Ball, S.; Halaki, M.; Orr, R. (Journal of Athletic Training, 2020)
Context: Rugby union is a field-based collision sport with high injury rates. Associations between injury characteristics and global positioning system-derived movement demands in rugby union athletes are yet to be investigated. Objective: To investigate associations between match injuries and movement demands, anthropometrics, and physical performance in under-20-years university-level rugby union players. Design: Descriptive epidemiology study. Setting: Competition season. Patients or Other Participants: Rugby union players (n = 34, age = 19.3 ± 0.6 years) from a university club were recruited. Main Outcome Measure(s): Acute medical attention non-time-loss (NTL), medical-attention time-loss (TL), and total medical-attention (MA) injuries sustained were recorded. Principal component (PC) analysis was performed on player-movement demand variables to identify independent-movement demand components. Pearson correlation and bivariate linear regression were used to test associations between match injuries and PCs. Anthropometric and physical performance measures were tested as predictors of match injuries using a forward stepwise multiple regression analysis. Results: Backs had lower anthropometric and performance measures than forwards (P < .05), whereas forwards performed fewer weekly movement demands than backs (P < .05). Increases in body mass and skinfold thickness were associated with more injuries (P < .05). Principal component analysis revealed 3 PCs representing overall performance, high-intensity running (HIR) performance, and impacts. Increases in HIR were associated with decreases in NTL upper limb and trunk (r = -0.32, P = .03), NTL musculoskeletal (r = -0.36, P = .05), NTL total (r = -0.46, P < .01), TL musculoskeletal (r = -0.30, P = .05), MA musculoskeletal (r = -0.41, P < .01), and MA total (r = -0.48, P < .01) injuries. Increases in impacts were associated with increased TL (r = 0.32, P = .03) and MA (r = 0.33, P = .03) head or neck injuries. Conclusions: Backs experienced greater weekly movement demands than forwards. Increases in HIR demands were associated with decreased acute injuries in university rugby players. Increases in impacts were associated with more acute head or neck injuries. Positional differences in movement demands, anthropometrics, and physical performance highlight the need for position-specific training.